Business Communication Skill Model Based on Internet of Thing (IoT). Issue 7 (March 2020) - Rozalena, A; Sulaeman, M; Mulyati, S; Gunawan, H
Abstract: This research is to construct business communication skills model based on Internet of Things (IoT). Business communicators need soft skills and hard skills. They are expected to increase marketing and network growth of customer markets in all industry lines. The purpose of this study are, (1) to describe the Internet of Things (IoT) based communication skills model; (2) to find out some new professions with the required communication skills in the business world. The methodology of this research is descriptive qualitative with the paradigm of analyzing literature through blog content and the appointment of informants using purposive sampling techniques. Researchers used document analysis with data analysis techniques using the interactive model of Miles and Huberman. The results of this study found, (1) the concept of communication skills that are able to realize a business communication model on an internet basis; (2) communication skills indicate the existence of activities in creating message designs with high creativity through internet-based work.